Ensinar Cidadania com Arte! Olha Para O Que Eu Faço ... Não Olhes Para O Que Eu Digo! Teaching Citizenship with Art! Look At What I Do ...Do not Look At What I Say! - Anabela Moura; Gabriela Barbosa (Escola Superior de Educação de Paula Frassinetti, 2018)
Neste artigo são abordadas questões relacionadas com o ensino do conceito de cidadania na Escola Superior de Educação, do Instituto Politécnico de Viana do Castelo, Portugal. Através da análise de práticas artísticas, propomo-nos determinar como conceitos de cultura, património, educação para o desenvolvimento, aprendizagem de serviço e direitos humanos na sociedade são abordados em atividades curriculares e como as perspetivas interdisciplinares são consideradas a via adequada para tais abordagens em termos de Educação Artística na Escola do século XXI  Teaching Citizenship with Art! Look At What I Do ...Do not Look At What I Say! Abstract This article will approach issues related to the teaching of the concept of citizenship according to Higher School of Education of the Polytechnic Institute of Viana do Castelo, Portugal. Through the analysis of artistic practices, we propose to determine how concepts of culture, heritage, education for development, service learning and human rights in society are addressed in curricular activities and how interdisciplinary perspectives are considered the appropriate way to such approaches in terms of Art Education in the 21st Century School. Keywords: Citizenship; Education for Development; Service - Learning; Artistic Education.